2013
DOI: 10.1080/20786204.2013.10874373
|View full text |Cite
|
Sign up to set email alerts
|

Utility of kangaroo mother care in preterm and low birthweight infants

Abstract: Preterm birth (< 37 completed weeks of gestation) is the largest direct cause of neonatal mortality, accounting for an estimated 27% of the 4-million neonatal deaths every year. Kangaroo mother care (KMC) is a type of care for preterm and premature infants whereby the infant is placed in an upright position against the parent's chest, with early skin-to-skin contact between the parent and infant. Mothers who practise KMC exhibit less maternal stress and fewer symptoms of depression, and have a better sense of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 69 publications
1
20
1
1
Order By: Relevance
“…Health centers were twice more likely to initiate KMC compared hospitals, and public facilities were also more likely to initiate KMC compared to private facilities. This result differs from other studies done in Malawi and South Africa that found higher KMC utilization in hospitals compared to lower-level facilities [19, 23]. In Ethiopia, LBW babies born in hospitals were more likely to be put in incubators.…”
Section: Discussioncontrasting
confidence: 92%
“…Health centers were twice more likely to initiate KMC compared hospitals, and public facilities were also more likely to initiate KMC compared to private facilities. This result differs from other studies done in Malawi and South Africa that found higher KMC utilization in hospitals compared to lower-level facilities [19, 23]. In Ethiopia, LBW babies born in hospitals were more likely to be put in incubators.…”
Section: Discussioncontrasting
confidence: 92%
“…This is in line with the previous systematic review studies in which KMC group initiated breastfeeding 1.6 days earlier than conventional neonatal care [10]. It was observed that infants who exposed to KMC showed significantly better emotion regulation than infants who exposed to the usual standard care which again initiated early breastfeeding [24, 25]. Furthermore, KMC has a significant role in starting breastfeeding among preterm and LBW infants [2628].…”
Section: Discussionsupporting
confidence: 87%
“…This finding was in line with study done in Zimbabwe, meta-analysis done by reviewing different literatures, and studies conducted in different parts of the world. [27][28][29][30] The reason for this is due to the fact that KMC increases mother to baby bonding, breastfeeding, and thermal protection better than conventional care and gives less opportunity for infections. In addition, immediate and exclusive breastfeeding serves as the starting point for a continuum of care for mother and newborn who can have long-lasting effects on health and development.…”
Section: Factors Associated With Neonatal Sepsismentioning
confidence: 99%